Consider the function f(x)= x(x-4)If the point , (2+ c,y) is on the graph of F(x), the following point will also be on the graph f(x)

(c- 2,y) or (2- c,y)

Answers

Answer 1
Answer:

Answer:

option (1) is correct.

point (c-2, y) lies on the graph of  f(x)=x(x-4).

Step-by-step explanation:

Given function f(x)=x(x-4) also point (2+ c,y) is on the graph of f(x) ,

We have to find out of given point which point will also be on the graph of f(x).

Consider  the given function f(x)=x(x-4)

f(x)=x(x-4) can be rewritten  f(x)=x^2-4x

Now we substitute the given point (2+ c, y) in the function given ,

we have,

f(x)=y=x(x-4)

put for x as 2+c , we have,

\Rightarrow y=(2+c)(2+c-4)

Solve, we get

\Rightarrow y=(2+c)(c-2)

Thus, both point (2+c, y) and (c-2, y) lies on the graph of  f(x)=x(x-4)

Thus, option (1) is correct.

Answer 2
Answer:

Final answer:

To determine whether the point (2+c, y) being on the graph of f(x) implies that the point (c-2, y) or (2-c, y) will also be on the graph of f(x), we need to substitute each point into the function and check if they satisfy the equation.

Explanation:

In this question, we are given the function f(x) = x(x-4). We need to determine whether the point (2+c, y) being on the graph of f(x) implies that the point (c-2, y) or (2-c, y) will also be on the graph of f(x). To verify this, we will substitute the given point (2+c, y) into the function and see if it satisfies the equation. Let's break it down step by step:

  1. Substitute the x-coordinate of the given point (2+c, y) into the function f(x).
  2. Simplify and solve the resulting equation for y.
  3. Substitute the x-coordinate of the points (c-2, y) and (2-c, y) into the function f(x) to check if they satisfy the equation.
  4. Based on the results, determine whether the given point implies that the other two points will also be on the graph of f(x).

Learn more about Graphing functions here:

brainly.com/question/32086455

#SPJ11


Related Questions

Please solve for x::)
Which function describes the graph in the picture? NEED HELP ASAP
There were 88 vendors at the craft fair. They needed to set up an equal number in each of the rows and needed 4 flags to mark each row. How many rows and flags were needed?
Simplify the expression given below.
What is the probability of rolling a product of 30 when rolling 2 six sided number cubes?

Hurry plz yeyeyeyeyeyye

Answers

Answer:

$250

Step-by-step explanation:

Solve for x. 12:15 = x:5

Answers

The value of x will be;

⇒ x = 4

What is Proportional?

Any relationship that is always in the same ratio and quantity which vary directly with each other is called the proportional.

Given that;

The expression is,

⇒ 12 : 15 = x : 5

Now,

Since, The expression is,

⇒ 12 : 15 = x : 5

Hence, Solve for x as;

⇒ 12 / 15 = x / 5

⇒ 12 × 5 / 15 = x

⇒ x = 12 / 3

⇒ x = 4

Thus, The value of x = 4

Learn more about the proportion visit:

brainly.com/question/870035

#SPJ2

15/3 = 5
12/3 = 4
x = 4

Write 9/12 as a decimal

Answers

9 / 12      3 into 9 is 3 and 3 into 12 is 4

= 3 / 4

= 0.75

Henry can build 2 birdhouses in 30 minutes. how many birdhouses can he build in 4 hours?

Answers

2 birdhouses in 30 minutes = 4 birdhouses per hr.

for 4 hrs......4 x 4 = 16 birdhouses in 4 hrs

A submarine submerged at a depth of −40 feet dives 57 feet more. What is the new depth of the submarine?

Answers

Answer:

-97 feet

Step-by-step explanation:

-40+-57=-97

Express the series using sigma notation. 6 + 9 + 12 + 15.

a
b
c
d

Answers

Answer:

Option (d) is correct.

6 + 9 + 12 +15 = \sum_(k=1)^(4)(3k+3)

Step-by-step explanation:

Consider the given series expansion 6 + 9 + 12 +15.

since we have to write in series form of 3.

We first write each term of given series in term of 3k or 3k+3

6 can be written as 3(2) or 3(1)+3

9 can be written as 3(3) or 3(2)+3

12 can be written as 3(4) or 3(3)+3

15 can be written as 3(5) or 3(4)+3

Thus, we can write the given series as ,

\sum_(k=2)^(5)3k or  \sum_(k=1)^(4)(3k+3)

Since, we have options to choose.

From the given option (d) matches our result.

So,  6 + 9 + 12 +15 = \sum_(k=1)^(4)(3k+3)


Answer:

D

Step-by-step explanation: